The Sanskrit and Arabic Sources of the Praśnatantra Attributed to Nīlakaṇṭha - Gansten, Martin (History of Science in South Asia, 2014)
The highly popular Praśnatantra attributed to Nīlakaṇṭha of Kāśī (fl. late 16th century) and sometimes regarded as the third volume of his Tājikanīlakaṇṭhī is shown to depend for its basic structure on an abridged Sanskrit version of the Kitāb fi l-masāʾil wa-l-aḥkām by Sahl ibn Bishr (early 9th century), apparently authored by Samarasiṃha in the 13th century, to which quotations primarily from Sanskrit astrological works in the classical Indian style have been added, resulting in a hybrid of Indian and Perso-Arabic interrogational astrology.